Regulatory effects of miR-28 on osteogenic differentiation of human bone marrow mesenchymal stem cells. Issue 1 (1st January 2022) - Wang, Min; Dai, Tianming; Meng, Qingqi; Wang, Wen; Li, Siming
ABSTRACT: We aimed to assess the regulatory effects of miR-28 on the osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMMSCs). HBMMSCs isolated, cultured and induced (at P3) to undergo osteogenic induction. The expressions of miRNAs were detected by gene microarray, and differentially expressed miRNAs in hBMMSCs compared with induced cells were obtained by significance analysis of microarrays. The microarray findings were confirmed by RT-PCR. TargetScan showed that signal transducer and activator of transcription 1 (STAT1) was the downstream target gene of miR-28. The relationship between miR-28 and STAT1 was validated using dual-luciferase reporter gene assay. HBMMSCs were transfected with miR-28 mimics and STAT1 siRNA, respectively. Samples were collected on day 10 after osteogenic differentiation, and the alkaline phosphatase (AKP) activity, Runt-related transcription factor 2 (RUNX2, a key regulator of osteogenic differentiation) and STAT1 expressions were determined using kits, PCR and Western blotting, respectively. Cell proliferation and migration were detected through CCK-8 and Transwell assays, respectively. During the osteogenic differentiation of hBMMSCs, the expression level of miR-28 increased. MiR-28 specifically bound the 3'-untranslated region (3'UTR) of STAT1 mRNA. It inhibited STAT1 expression in a targeted manner during osteogenic differentiation. Interference with STAT1 partially mimicked the regulatory effects of miR-28 overexpression on the osteogenic differentiation of hBMMSCs. Interference with STAT1 or overexpression of miR-28 did not affect proliferation or migration. MiR-28 has gradually increased expression during the osteogenic differentiation of hBMMSCs, which can directly bind STAT1 3'UTR and inhibit its expression, thereby up-regulating AKP and RUNX2, and promoting osteogenic differentiation.